Gravesʼ Ophthalmopathy in a Paediatric Population - Sadeghi, Y.; Obéric, A.; Theintz, G.; Hamédani, M. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Gravesʼ disease is an autoimmune disorder leading to hyperthyroidism. It is often associated with ophthalmic manifestations. Gravesʼ disease is reported to be rare in the paediatric population. Patients and Methods We performed a retrospective analysis on all patients diagnosed with ophthalmopathy related to Gravesʼ disease at a paediatric age (less than 18 years old) in our institution between 2004 and 2015. Results Eight patients were identified: 6 females and 2 males. The median age at diagnosis was 11.5 years (range 3–16). Ophthalmic signs were: proptosis (6/8), superficial punctate keratitis (5/8), eyelid retraction (4/8), lagophthalmos (2/8), and oculomotor dysfunction (2/8). No patients showed signs of complication such as ocular hypertension or compressive optic neuropathy. Orbital decompression was performed in one patient in a non-emergency setting. Conclusion Ophthalmic involvement in Gravesʼ disease is rarely encountered in paediatric patients. Ophthalmologists should be aware of this entity to ensure that patients with thyroid dysfunction are identified at an early point in time.
Keywords: Gravesʼ disease; Gravesʼ ophthalmopathy; Gravesʼ orbitopathy; thyroid-associated ophthalmopathy; thyroid-associated orbitopathy; thyroid eye disease; Basedow; paediatric